A cyclic plastic-damage multiphase model for evaluation of multiple cracking in strain hardening cementitious composites. (January 2022) - Liu, Wei-He; Zhang, Lu-Wen; Liew, K.M.
Abstract: Multiple cracking, if formed in an inherently brittle cementitious composite, remarkably boosts its ductility and leads to the desired strain hardening material during tension. The key to predicting multi-crack growth and, ultimately, tuning the composite's tensile properties primarily lies in resolving the competitive propagation of closely spaced microcracks, strung by fibers. A mechanism-based multiphase approach is developed, enabling clarification of the realistic multiple microcracks bridging mechanism arising from the stacked fiber bundles within strain hardening cementitious composites. The proposed multiphase configuration framework establishes reliable models for bridging fiber bundles, interface constitution and matrix cracks, which are critical in all types of fractures, and confronts new challenges arising from competitive opening of stringing cracks. The study has the following novelties: (1) Regarding matrix cracking, a new damage plastic interface model is proposed to characterize the stiffness degradation and gradual recovery of contact stiffness for cementitious composites during cyclic loading. (2) Targeting the crack resistance effect, a unified nonlinear bond-friction model is formulated which is able to capture the elastic bond breaking, friction hardening, fiber rupture, fiber pullout and the cyclic loading behavior of the fiber/matrix interface, simultaneously. (3) Considering the snubbing effect that is intrinsic to cracks, a two-stage evolution algorithm for the fiber bridging force is implemented which distinguishes the bridging efficiency in an intact and cracked medium. We accurately predict the tensile cracking and capture the strain hardening of composites with individual constituent properties, providing further microscopic effects beyond the experimental scope, such as the fiber and matrix stress distributions, through which the development of residual compressive traction in matrix cracks is identified for the first time. This work could serve as a new guide for designing strain hardening cementitious composites with optimal performances.